2012
DOI: 10.1039/c2cp23237e
|View full text |Cite
|
Sign up to set email alerts
|

The nature of cationic adsorption sites in alkaline zeolites—single, dual and multiple cation sites

Abstract: Gas adsorption on zeolites constitutes the base of many technological applications of these versatile porous materials. Quite often, especially when dealing with small molecules, individual extra-framework (exchangeable) cations are considered to be the adsorption site on which molecules coming from a gas phase form the corresponding adsorption complex. Nonetheless, while that can be the case in some instances, recent research work that combines variable temperature infrared spectroscopy with periodic DFT calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 166 publications
(200 reference statements)
5
64
0
1
Order By: Relevance
“…2-IE is presumably due to the predominant formation of dual cation sites, in which two neighboring Na cations complementary interact with one CO 2 molecule. The possibility of CO 2 interaction with dual cations was proposed by Nachtigall and Cejka [66,69,70], in which they controlled the homogeneity of Al distribution in Na-FER (model zeolite with Si/Al ¼ 15.7) by changing the type of organic structure-directing agents during the synthesis [66]. When Al sites were distributed homogeneously in the vicinity of Na cations, one Na cation can interact with an average of one CO 2 molecule where the isosteric heat of adsorption is in the range of 42e47 kJ mol À1 (depending on Al T-site location) [66].…”
Section: Differences In Co 2 Adsorption Properties For Osda-free and mentioning
confidence: 98%
“…2-IE is presumably due to the predominant formation of dual cation sites, in which two neighboring Na cations complementary interact with one CO 2 molecule. The possibility of CO 2 interaction with dual cations was proposed by Nachtigall and Cejka [66,69,70], in which they controlled the homogeneity of Al distribution in Na-FER (model zeolite with Si/Al ¼ 15.7) by changing the type of organic structure-directing agents during the synthesis [66]. When Al sites were distributed homogeneously in the vicinity of Na cations, one Na cation can interact with an average of one CO 2 molecule where the isosteric heat of adsorption is in the range of 42e47 kJ mol À1 (depending on Al T-site location) [66].…”
Section: Differences In Co 2 Adsorption Properties For Osda-free and mentioning
confidence: 98%
“…The weak interaction of CO 2 with surface of Al-SBA-15 silica was also reported [22]. In addition, the size of the pores is too large to influence the adsorption by the effect ''from the top'' as recently described by Nachtigall et al [39,40] and which is so important in the case of CO 2 adsorption in microporous zeolites. The CO 2 isotherms on modified samples exhibit nonlinear concave decreasing course typical for adsorption of CO 2 on inorganic materials (zeolites, mesoporous adsorbents, hydrotalcite-like compounds.)…”
Section: Adsorption Of Carbon Dioxidementioning
confidence: 73%
“…The smaller values found herein for the investigated (Na,Cd)-MOF suggest a weaker (local) interaction of the CO 2 molecule with the Na + cation. However, analysis of fine details cannot be done at this stage, because it was shown that for CO 2 adsorbed on both, MOFs and zeolites alike, at least one half of the gas-solid interaction energy comes from long range dispersion interactions, 25,55,56 and the actual value of H 0 depends on a complex interplay of electrostatic and dispersion forces. Adsorption selectivity, of carbon dioxide versus nitrogen, referred to post-combustion flue gas that (besides other minor components) usually contains CO 2 and N 2 at a partial pressure of about 0.15 and 0.75 bar, respectively, is commonly assessed from single-component gas adsorption isotherms (at 298 K) by using the selectivity factor, S, expressed as: 2,11 (4) where q i and p i are the molar fraction and partial pressure, respectively, of component i.…”
Section: Resultsmentioning
confidence: 99%